Projeto e desenvolvimento de um retificador trifásico com fator de potência unitário utilizando conversores cúk isolados com controle ativo de corrente de entrada e autotransformador de 12 pulsos com conexão delta diferencial - Soares, Ana Lúcia (2019)
The use of electronic components is increasingly intensifying and, with it there is an increase in harmonic distortions impairing the quality of electricity. Aiming at reducing this problem, this work presents a 12-pulse rectifier with two 1000 W Cuk DC-DC converters in each. It operates in continuous driving mode, has galvanic isolation, capacitive energy transfer, high power factor and low harmonic distortion in the converter input current. The use of the non-insulated autotransformer contributes to the reduction of the weight and volume of the structure, since the high frequency isolation is performed in the intermediate stage through the Cuk converter which has a considerably small transformer, ensuring the balance between each rectifier group and regulating the frequency. output voltage. This topology can be used in battery chargers, electric machine drives, telecommunications applications, retrofit and more electric aircraft (MEA), in equipment that was driven by hydraulic, pneumatic or mechanical structures. This work deals in detail with the development of digital hysteresis control with triangular current imposition on the input inductors of each Cuk converter, in order to regulate the output voltage and balance the power processing between each rectifier group. To validate the proposal, computational and experimental results were obtained through the construction of a prototype.